2006
DOI: 10.1002/adma.200502286
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Optical Lithography for Photonic Microstructures

Abstract: Microcavities[1] and waveguides [2] operating within the optical bandgap of a photonic crystal [3,4] have the potential to create integrated optical devices capable of all-optical signal processing. [5] To achieve this degree of control over visible or near-infrared light is a materials-engineering challenge requiring precise local modification of wavelength-scale microstructure.In this communication we demonstrate a rapid and flexible technique for optical fabrication by creating a device embedded in, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 32 publications
(45 reference statements)
0
53
0
7
Order By: Relevance
“…Second, addition of optically active defects into the photoresist prior to development via laser direct writing is possible. The direct writing of features in holographic PhCs has now been demonstrated in both 2D [87] and 3D [88] structures (Fig. 8).…”
Section: Holographic Lithographymentioning
confidence: 99%
See 2 more Smart Citations
“…Second, addition of optically active defects into the photoresist prior to development via laser direct writing is possible. The direct writing of features in holographic PhCs has now been demonstrated in both 2D [87] and 3D [88] structures (Fig. 8).…”
Section: Holographic Lithographymentioning
confidence: 99%
“…[132] When performed in conjunction with in situ fluorescence confocal imaging, it is possible to pinpoint the location of the TPP features with respect to the PhC lattice. [88] An important consideration for any cPBG application is the ability to convert the PhC to a high-refractive-index structure that exhibits a cPBG. Generally, this is accomplished for colloidal PhCs through infiltration with a high-index material such as Si at an elevated temperature, followed by removal of the silica, resulting in an inverse opal structure.…”
Section: D Embedded Defects Via Multistep Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Figure 6(b) demonstrates a multi-step procedure to create more complex composite patterns. Others have combined MBIL with various lithographic techniques including other mask-based techniques (e.g., proximity or contact lithography) [159,173], electron-beam lithography [81,174,175], electron-beam-induced deposition [176], focused ion-beam lithography [155,177], direct laser writing [77,150,178,179], atomic force microscopy nano-indentation [180], and multi-photon polymerization [181][182][183]. For example, interference lithography has been combined with optical contact lithography to fabricate triple-gate metal-oxide-semiconductor field effect transistors [161].…”
Section: Multi-beam Interference Lithography and Nano-electronicsmentioning
confidence: 99%
“…Two-photon ablation or polymerization was used to create defects in PhC template in SU-8, which were created through holographic lithography, by three research groups in 2005, 18 2006, 19 and 2008. 20 Sun et al 18 demonstrated the hybrid holographic and direct writing method in a two-dimensionally periodic structure while Scrimgeour et al 19 described the creation of defect structures inside 3D PhCs. The other group 20 fabricated and developed polymer-air PhCs in SU-8 via holographic lithography and the PhCs were infiltrated with trimethylol propane triacrylate and a two-photon sensitive photoinitiator for the direct writing of defects via an ultrafast laser.…”
Section: Photonic Crystals With Defect Structures Fabricated Through mentioning
confidence: 99%